Halal Certification Value Chain in Brunei Darussalam - Nor Surilawana Haji Sulaiman; Norkhairiah Hashim (Dinar : Jurnal Ekonomi dan Keuangan Islam, 2021)
As Brunei Darussalam is positioning itself to be a halal hub, Brunei needs to act fast to strengthen its halal certification value-chain or system. Therefore, the Brunei Government appointed Bahagian Kawalan Makanan Halal (Halal Food Control Division), Jabatan Hal Ehwal Syariah (Department of Shariah Affairs), as a body to handle the halal certification process. Due to the rapid growth of the halal industry both local and international, it is important to research the halal certification process. The main objective of this study is to provide an understanding of the halal certification process in Brunei Darussalam. The study will highlight and determine to examine (1) the halal certification process, (2) actors, and (3) information on halal. The method used in this study is derived from the literature review in the form of related articles, journals, proceedings and books, and interviews with related actors of the halal certification. The results of the study will reveal (1) the halal certification value chain, (2) the related agencies and acts of the halal certification process, and (3) the information required in applying halal certification in Brunei Darussalam.